PENGARUH PROFESIONALISME, KARAKTERISTIK PEKERJAAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS SOSIAL KABUPATEN LABUHANBATU UTARA - Andri Junasri Tanjung; Muhammad Ali Imran; Winda Santi Dalimunthe; Sarifah Hanum Lubis; Ucok Syahputra (Universitas Islam Islam Sumatera Utara, 2020)
The purpose of this research is to analyze, the influence of professionalism on the performance of employees in the Social Service Of North Labuhanbatu Regency, the influence of work characteristics on the performance of employees in the Social Service of North Labuhanbatu Regency, the influence of organizational commitment to the performance of employees in the Social Service of North Labuhanbatu Regency and the influence of professionalism, characteristics of work and organizational commitment to the performance of employees in the Social Service of North Labuhanbatu Regency. Sampling techniques in this study is total sampling, namely all employees in the Social Service Of North Labuhanbatu Regency of 42 people. Analysis techniques used are descriptive analysis methods and multiple linear regression analysis, Variable Research Results professionalism, characteristic work and organizational commitment simultaneously have a significant effect on the performance of employees in working in the Social Service North Labuhanbatu Regency, Variable professionalism partially no significant influence on the performance of employees in the Social Service North Labuhanbatu Regency, variable characterisstic work partially no significant influence on the performance of employees in the Social Service North Labuhanbatu Regency , the organizational commitment variable is partially there is a significant influence on the performance of employees in the Social Service North Labuhanbatu Regency. Professionalism, job characteristics and organizational commitment were able to explain the effect on employee performance by 61.4%, while the remaining 39.6% were explained by other variables not studied in this study.